MODERN TRENDS IN TRANSLATION STUDIES AND PRACTICES IN INDIA: BRIDGING LINGUISTIC DIVERSITY IN A DIGITAL AGE (KONFERENSIYA, 2025)
India's linguistic landscape, characterized by over 22 official languages andthousands of dialects, positions translation as a critical tool for cultural preservation,economic integration, and technological advancement. This paper explores moderntrends in translation within the Indian context, focusing on the integration of artificialintelligence (AI), the resurgence of literary translation, audiovisual practices, andlocalization efforts. Drawing on recent scholarly works, government policies, andindustry reports from 2023–2025, it examines how these trends addressmultilingualism while navigating challenges like data scarcity and cultural nuances.Key findings highlight the hybrid AI-human model as a dominant paradigm, theglobal recognition of Indian literary translations, and policy-driven initiatives forindigenous language support. The analysis underscores opportunities for equitableknowledge dissemination but warns of persistent barriers in low-resource languages.Recommendations include enhanced investment in AI training datasets andcollaborative translation ecosystems to foster inclusivity